Development of a culturally appropriate health-related quality of life measure for human immunodeficiency virus-infected children in Thailand - Warunee Punpanich (2018)
Aim: Develop a reliable and valid self-report health-related quality of life (HRQOL) instrument for human immunodeficiency virus (HIV)-infected children in Thailand. Methods: The Thai Quality of Life for HIV-infected Children instrument, the ThQLHC (an HRQOL measure that uses the Pediatric Quality of Life Inventory as a generic core and a 17-item HIV-targeted scale), was developed and administered cross-sectionally to 292 HIV-infected children in Thailand. The disease-targeted scale included HIV-related symptoms, ability to adhere with their treatment regimens and self-image. The internal consistency reliability (Cronbach's α) and construct validity of the ThQLHC scales were then evaluated. Results: Internal consistency reliability coefficients ranged from 0.57 to 0.82, with four of five scales reaching the minimal acceptable level ( > 0.70). Significant associations were found between poor HRQOL and poor self-rated disease severity, care giver's rated overall quality of life, cluster of differentiation (CD) 4 percent and plasma HIV ribonucleic acid level. Conclusion: Reliable and valid disease-targeted HRQOL measures for HIV-infected children are essential in the assessment of therapeutic effectiveness. The findings of this cross-sectional survey provide support for the reliability and validity of the ThQLHC as an HRQOL outcome measure for HIV-infected Thai children. © 2010 The Authors. Journal of Paediatrics and Child Health © 2010 Paediatrics and Child Health Division (Royal Australasian College of Physicians).